Determinants factors for social media policy adoption in Malaysian SMEs: literature review - Halil, Nur Afni; Bidin, Rosmiza; Osman, Nizam; Shekh Alsagoff, Syed Agil (Academic Inspired Network, 2021)
Recently, research on the social media has been widely discussed by the scholars in many fields. The use of social in business enable the organisation to communicate with their stakeholders, save time in terms of business processes, reduce barriers and geographical restrictions and others. Thus, many businesses adopt social media as one of their marketing tools including Malaysian SMEs to carry out their marketing activities. Although social media proved to provide tremendous benefits to the organisation, the challenges of using social media were found. Strategic failure and lack of understanding of social media can damage and tarnish the organisation’s reputation. Thus, having a social media policy or guiding principles on social media could shape employee’s actions and address challenges to the development. Therefore, this study was developed and integrated the factors that lead to the social media policy adoption. The outcome of this research will reveal the effectiveness of the social media policy adoption based on few elements such as knowledge, organisation culture and perceived characteristics of the policy.